2010
DOI: 10.1111/j.1755-3768.2010.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of dry eye disease: a nationwide population‐based study

Abstract: . Purpose:  To investigate the comorbidities of dry eye disease in a nationwide population‐based data in Taiwan. Methods:  This study features a study group and a comparison group. The study group comprised 12 007 patients who sought ambulatory care for treatment of dry eye in 2005 and 2006. In total, 36 021 randomly selected patients were in the comparison group. Conditional logistic regression analyses conditioned on gender, age, monthly income and level of urbanization of the community in which the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 30 publications
11
81
1
Order By: Relevance
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…However, to the best of our knowledge, no study has ever examined the relationship between DED and QOL in non-clinic-based subjects in Japan, whereas DED has been reported to be related to poor QOL and depression in a general population in other countries (Galor et al 2011;Le et al 2012;Wang et al 2012). The major purpose of the present study is, therefore, clarify the relationship between DED and QOL in non-clinic-based Japanese subjects.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indirect proof of an association between hypercholesterolemia and the tear lipidome is provided by the reported cases of "jelly-bump" lipid contact lens deposits in patients with elevated intakes of protein, alcohol and cholesterol (Hart et al, 1987(Hart et al, , 1986. Hypercholesterolemia was associated with dry eye in the Beaver Dam Eye Study (Moss et al, 2000) and in the Taiwan nationwide populationbased survey (Wang et al, 2012). A retrospective case-control study in patients with meibomian gland dysfunction identified dislipidemia as a positive risk factor; surprisingly, elevated HDL contributed the most risk for meibomian gland dysfunction (Dao et al, 2010).…”
Section: Obesity-related Disorders: Dislipidemia and Hyperglycemiamentioning
confidence: 93%
“…Based on OSDI score, the ocular surface is defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33-100) [44]. It is noteworthy that although the OSDI is not routinely used in clinical practice, it has been shown to be valid and reliable to quantify the impact of dry eye on the quality of life [44].…”
Section: Discussionmentioning
confidence: 99%